Linguistociative Aspects of Communicative Interaction in Learning the Russian Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This thesis analyzes the linguocultural aspects of communicative communication in the study of the Russian language. Communication in the Russian language is not based only on grammar and vocabulary, but it is also necessary to take into account cultural, social and psychological factors in language learning. It discusses the importance of language learners' understanding of the traditions, national mentality and contextual features of the Russian language in effective language learning. It also examines the differences between formal and informal communication in language learning and the influence of cultural values on the language.